Detection of Adulterants Metanil Yellow in Turmeric Powder Using Fourier Transform Infrared (FTIR) Spectroscopy Combined with Chemometrics OPLS-DA and PLS - Dia, Syahril Maulid; Putri, Anggita Rosiana; Muchlashi, Luthfi Ahmad (Universitas Islam Indonesia, 2024)
Turmeric powder (Curcuma longa L.) is often used for food coloring and flavoring. The high demand for turmeric powder has led to adulteration, one of which is metanil yellow. This study aims to detect metanil yellow dye in turmeric powder using Infrared Spectroscopy (FT-IR) and Chemometrics. The chemometrics model was built by preparing turmeric powder and metanil yellow in the concentration range of 0-50% (w/w). Data was processed using multivariate calibration using OPLS-DA (Orthogonal Partial Least Squares Discriminant Analysis) and PLS (Partial Last Square). The results obtained from OPLS-DA processing of market samples 1 and 2 are estimated to be pure turmeric powder, and samples 3 to 10 are adulterated. From the PLS results, the best calibration model was obtained at wave numbers 1199-539 cm-1 with R2 values for calibration and validation of 0.9967 and 0.9970, respectively, with RMSEC of 2.48 and RMSEP of 6.35. The PLS results showed that in sample 3 containing metanil yellow, in samples 4 to 10, no metanil yellow was detected. The ingredients added were not metanil yellow. It was concluded that FTIR combined with chemometrics could detect the metanil yellow in turmeric powder.